Islam Moderat di Pesantren: Sistem Pendidikan, Tantangan, dan Prospeknya - Ajibah Quroti Aini (Edukasia Islamika, 2018)
This present study aims to expose values of moderate Islam in pesantren (Islamic boarding school). Pesantren constitutes a traditional Islamic educational institution that has grown and developed among Indonesia’s Muslim societies. The institution gives a very significant contribution to the development of Islamic education in particular as well as the implementation of national education system in general. A qualitative descriptive approach was designed in this library research. The findings promote that pesantren has implemented the traditional education system that obliges santri (pesantren students) to live in a boarding school setting. They learn Islamic studies under the supervision of kyai (pesantren teachers). This study also promotes that pesantren plays a pivotal role in fostering values of moderate Islam as one of the national challenges nowadays. The values highlight tolerance in understanding diversity to realize a peaceful life. The today’s condition showing the development of pesantren can be used as the prospect for Muslims to spread the concept of moderate Islam that leads us not to be easily provoked by hoaxes. It implies that values of moderate Islam need to be sustainably promoted in pesantren as an Islamic education institution.